Climatic responses on thermal design of buildings for energy efficiency: comparative study for Taman Negara Pahang and other microclimates / Nor Zaini Ikrom Zakaria, Sabarinah Sh Ahmad and Zakiah Mohamed - Ikrom Zakaria, Nor Zaini (Research Management Institute (RMI), 2011)
The alarm about global warming has galvanised the international community towards formulating global agreements to address the emerging related issues on humankind and environment (United-Nations, 2006a, 2006b, 2004). In the aspiration for Vision 2020, the Government of Malaysia has included sustainable development as one of the development thrusts in the 8th and 9th Malaysian Plan. In the area of built environment, sustainable development includes energy resources and the efficient usage that have various short-term and long term impacts on the environments and thus the humankind.